Rete Middle Cerebral Artery Anomaly Presenting with a Large Intracerebral Hemorrhage: A Case Report - Chandra Dev Sahu; Nishant Bhargava; Debabrata Sahana; Sanjeev Kumar (Journal of Clinical Interventional Radiology ISVIR)
Rete MCA anomaly is extremely rare and has been seldomly discussed in literature. Embryologically MCA develops by fusion of multiple twigs which form a single channel. If there is failure to fuse a plexiform network of vessels persists known as rete MCA. This web like network of vessels is at high risk of haemorrhagic stroke and therefore for patients presenting incidentally correct diagnosis is paramount. Here we report a case of rete MCA anomaly in a 35-year-old gentle man who presented with a large haemorrhagic stroke in emergency. DSA showed unilateral involvement of proximal MCA, and otherwise normal intra-cranial vasculature. With this report we aim to correctly diagnose this rare condition and avoid misdiagnosis leading to unnecessary treatments.